Caregiver monitoring, but not caregiver warmth, is associated with general cognition in two large sub‐samples of youth. Issue 3 (11th November 2022) - Keller, Arielle S.; Mackey, Allyson P.; Pines, Adam; Fair, Damien; Feczko, Eric; Hoffmann, Mauricio S.; Salum, Giovanni A.; Barzilay, Ran; Satterthwaite, Theodore D.
Abstract: Individual differences in cognitive abilities emerge early during development, and children with poorer cognition are at increased risk for adverse outcomes as they enter adolescence. Caregiving plays an important role in supporting cognitive development, yet it remains unclear how specific types of caregiving behaviors may shape cognition, highlighting the need for large‐scale studies. In the present study, we characterized replicable yet specific associations between caregiving behaviors and cognition in two large sub‐samples of children ages 9—10 years old from the Adolescent Brain Cognitive Development Study ® (ABCD). Across both discovery and replication sub‐samples, we found that child reports of caregiver monitoring (supervision or regular knowledge of the child's whereabouts) were positively associated with general cognition abilities, after covarying for age, sex, household income, neighborhood deprivation, and parental education. This association was specific to the type of caregiving behavior (caregiver monitoring, but not caregiver warmth), and was most strongly associated with a broad domain of general cognition (but not executive function or learning/memory). Additionally, we found that caregiver monitoring partially mediated the association between household income and cognition, furthering our understanding of how socioeconomic disparities may contribute to disadvantages in cognitive development. Together, these findings underscore the influence of differences in caregiving behavior in shaping youth cognition. Research Highlights: Caregiver monitoring, but not caregiver warmth, is associated with cognitive performance in youth Caregiver monitoring partially mediates the association between household income and cognition Results replicated across two large matched samples from the Adolescent Brain Cognitive Development Study ® (ABCD) Abstract : Caregiving plays an important role in supporting cognitive development, yet it remains unclear how specific types of caregiving behaviors may shape cognition, highlighting the need for large‐scale studies. Replicating findings across two large sub‐sample of children ages 9‐10 years old, we found that child reports of caregiver warmth were positively associated with general cognition abilities. Additionally, we found that caregiver monitoring partially mediated the association between household income and cognition, furthering our understanding of how socioeconomic disparities may contribute to disadvantages in cognitive development.